2021
DOI: 10.5772/intechopen.98552
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Protein Kinase and Its Inhibitor: A Review

Abstract: Deregulation of a broad range of protein kinases has been linked to the development and growth of cancer cells. Protein kinases are intracellular enzymes that regulate cell growth and proliferation as well as the triggering and regulation of immune responses. Protein kinases are important therapeutic targets in cancer because of their critical role in signalling mechanisms that drive malignant cell characteristics. Intensive efforts in drug research have been made in this area over the last two decades. The cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Furthermore, it was reported that kinases are among the major targets of polyphenols [ 49 ]. Protein kinases are important therapeutic targets in cancer because of their critical role in signaling mechanisms that drive malignant cell characteristics [ 55 ]. They have the potential to bind to ATP-binding sites thereby modulating the action of mitogen-activated protein kinase (MAPK), phosphoinositide 3-kinase (PI3K), Akt/protein kinase B (Akt/PKB), tyrosine kinases, and protein kinase C (PKC) pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that kinases are among the major targets of polyphenols [ 49 ]. Protein kinases are important therapeutic targets in cancer because of their critical role in signaling mechanisms that drive malignant cell characteristics [ 55 ]. They have the potential to bind to ATP-binding sites thereby modulating the action of mitogen-activated protein kinase (MAPK), phosphoinositide 3-kinase (PI3K), Akt/protein kinase B (Akt/PKB), tyrosine kinases, and protein kinase C (PKC) pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Human protein kinases have been divided into nine classes which are further subdivided into families, and often subfamilies whose actions can alter up to 30% of all cell proteins [ 22 ]. The molecular shifts exerted by them through phosphorylation not only can affect the function of a given protein, but it can also stabilize it, localize it in a particular cellular compartment and modulate its association with other proteins [ 23 ].…”
Section: Kinases As Cancer Driversmentioning
confidence: 99%
“…Playing fundamental roles in cell division, survival and migration, their dysregulation is commonly associated with human malignancies and contributes to tumor initiation and all stages of cancer progression. In fact, innumerous mutations, translocations, and amplifications that result in constitutively overexpressed or active kinases have been demonstrated in many human cancers [ 23 ]. Mutations within the catalytic domain serve to stabilize the kinase in an active conformation and to destabilize cis-inhibitory interactions.…”
Section: Kinases As Cancer Driversmentioning
confidence: 99%
“…PKC also has a role in the progression of insulin tolerance and DM through the regulation of the proliferation and activity of β-cells, and also through insulin secretion and cell death. During pancreatitis, PKC is released following pancreatic injury and inflammation with trypsinogen activation and basolateral exocytosis ( Theivendren et al, 2021 ).…”
Section: Protein Kinase C (Pkc) Pathwaymentioning
confidence: 99%